Groups of companies and jurisdiction in the context of the private enforcement of Competition Law of the European Union - Marino, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This contribution analyses the cross borders effects of the concept of economic unit within EU competition law. The CJEU’s case in Sumal offers the opportunity to investigate the applicability and the impact of the concept within the private enforcement. Then, the effects of the application of regulation No. 1215/2012 and of regulation No. 864/2007 are analysed with regard to the antitrust infringements with cross borders implications, in order to examine finally the favourable impact for the protection in favour of the victims, with particular regard to consumers, driven by the concept.
Keywords: private enforcement of EU competition law; concept of economic unity; jurisdiction in torts; special jurisdiction for the operation of a branch, an agency or any other establishment; law applicable to acts restricting free competition